2023
DOI: 10.3390/met13111824
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining Excellent Mechanical Properties in an Ultrahigh-Strength Stainless Bearing Steel via Solution Treatment

Kai Zheng,
Zhenqian Zhong,
Hui Wang
et al.

Abstract: A novel versatile ultrahigh-strength stainless bearing steel was prepared by first solution treating the steel at temperatures between 1000 °C and 1100 °C for 1 h, followed by performing cryogenic treatment at −73 °C for 2 h, and tempering at 500 °C for 2 h, with the cryogenic and tempering treatments being repeated twice. The microstructures were characterized using multiscale techniques, and the mechanical properties were investigated using tensile testing, as well as via Rockwell hardness and impact toughne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Extensive research has been done in the field of additive manufacturing, where one approach was to add a stainless steel layer to a base of less valuable steel, which leads to a hybrid steel-steel component. Also, the effects of treating stainless steel with a solution in order to make it more durable and therefore more suitable for bearing applications have been investigated [21].…”
Section: Martensitic Phase Transformation In Forgingmentioning
confidence: 99%
“…Extensive research has been done in the field of additive manufacturing, where one approach was to add a stainless steel layer to a base of less valuable steel, which leads to a hybrid steel-steel component. Also, the effects of treating stainless steel with a solution in order to make it more durable and therefore more suitable for bearing applications have been investigated [21].…”
Section: Martensitic Phase Transformation In Forgingmentioning
confidence: 99%
“…The test results on W6 high-speed steel after cryogenic treatment at −150 • C for 12 h have shown that the formation of fine carbides, uniformly distributed in the steel, reduces the dislocation stress and ultimately affects the macroscopic residual stress [20]. In addition, cryogenic treatment is widely applied to stainless steels [21], magnesium alloys [22], titanium alloys [23] and others. Therefore, it is necessary to study the influence of rolling deformation and cryogenic treatment on microstructure and properties.…”
Section: Introductionmentioning
confidence: 99%